Study of Lead-Free Solder Joint Reliability - Hana Mutialif Maulidiah; Budiana Budiana; Widya Rika Puspita; Adlian Jefiza; Mustanir Mustanir (JURNAL INTEGRASI, 2022)
Solders are essential for the construction of many engineering materials. The use of soldering in electronic packaging has become increasingly critical in today's world. In the electronic manufacturing industry, alternative soldering materials based on tin metal have developed gradually over the last two decades. Manufacturing companies are primarily concerned about removing lead from electronic manufacturing and waste recycling by switching to the lead-free solder. Environmental and human health are adversely affected by exposure to high lead levels in consumer products. The manufacturing industry has switched to lead-free soldering to support their social responsibility initiatives. The three categories of lead-free solder are classified according to temperature range: high-temperature solder, medium-temperature solder, and low-temperature solder. This research is conducted based on the approach of study literature, which is obtained from some papers that generally explain lead-free solder. To provide additional knowledge which is expected to add new insights about the importance of lead-free usage and its behavior.